The Labor Market in Poland and the Social Responsibility of the State and Business: Comparative Aspects - Krajewska, Anna; Krajewski, Stefan (Comparative Economic Research. Central and Eastern Europe, 2020)
Since the beginning of the transformation of the Polish economy, Many disturbing phenomena have appeared on the labour market in Poland. This paper points out to several of them, namely: 1) inconsistency in respecting the rules of the market mechanism and the important role of political decisions, 2) long-term persistence of high unemployment rate and low effectiveness of methods of combating unemployment, 3) low wages and rising income diversification, 4) high share of non-standard forms of employment in total employment. The scale of these disturbing phenomena is bigger than in other economies under transformation. In response to the imperfections of the market, many publications concerning corporate social responsibility appeared in Poland. According to the authors the reasons for the shortcomings of the labour market discussed in the paper should, however, be sought not only in the non-respect of the principles of corporate social responsibility, but also in the weaknesses of the adopted systemic solutions and weaknesses of institutions of the State.